Significant improvement on selectivity and capacity of glycine-modified FeCo-layered double hydroxides in the removal of As (V) from polluted water. (October 2021) - Shi, Xiaofeng; Hong, Junmao; Kang, Le; Song, Gang; Lin, Jing; Mai, Xianmin; Naik, Nithesh; Guo, Zhanhu
Abstract: A series of novel Fe/Co layered double hydroxides modified with glycine (named as FeCo-LDH@G) were prepared and served as high-performance adsorbents for As (V). With a Fe/Co mole ratio of 1:1, the Fe0·02 Co0.02 -LDH@G adsorbents achieved significant improvements on the adsorption selectivity and capacity for As (V). The As (V) adsorption by Fe0·02 Co0.02 -LDH@G follows Langmuir isotherm model and pseudo-second-order kinetics model. The maximum adsorption capacity is 820 mg g −1 and the equilibrium reaches in 120 min. Under the assistance of electrochemical devices, the Fe0·02 Co0.02 -LDH@G adsorbent was regenerated and the adsorption capacity for As (V) was dropped only about 13.41% in 5 cycles. These excellent performances make Fe0·02 Co0.02 -LDH@G as promising As (V) adsorbents for commercial wastewater treatments. Graphical abstract: Image 1 Highlights: Glycine-modified Fe/Co-layered double hydroxides (FeCo-LDH@G) were prepared. With clear boundaries, Fe0·02 Co0.02 -LDH@G has an excellent structure for adsorption. Fe0·02 Co0.02 -LDH@G has high capacity and selectivity on the adsorption of As (V). Fe0·02 Co0.02 -LDH@G shows excellent regeneration ability on the adsorption of As (V).